Pengaruh Penerapan Green Accounting, Kinerja Lingkungan dan Struktur Modal terhadap Kinerja Keuangan - Luthfiah Nur'aini; Hijroh Rokhayati (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2025)
This study aims to analyze the effect of implementation green accounting, environmental performance, and capital structure on financial performance. The theories used in this study are stakeholder theory and pecking order theory. This is a quantitative study using secondary data. The study population includes non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The sample selection used a purposive sampling method, resulting in 85 observations. Financial performance is measured using Return on Assets (ROA), green accounting is proxied by total environmental costs, environmental performance is measured by the PROPER rating, and capital structure uses the Debt to Equity Ratio (DER). Data analysis was performed using the EViews application version 13 through the stages of descriptive statistical analysis, classical assumption tests, panel data regression, model feasibility tests, and hypothesis testing. The results show that green accounting and environmental performance have no effect on financial performance, while capital structure has a negative effect on the financial performance of non-cyclical consumer companies.